Implementation of Combination of Curcumin Gel and Honey for the Treatment of Diabetic Foot Ulcer: A Pre-Experimental Study - Ivan Khalid Ibrahim; Ahmad Antoni; Indah Susanti (Journal of Wound Research and Technology, 2024)
Background: A persistent condition known as diabetes mellitus causes elevated blood sugar levels due to the pancreas's inability to make insulin. Diabetic foot ulcers are one consequence. Diabetic wounds can heal more quickly with the help of aloe vera and honey. Aims: This study aims to determine the effect of wound care using curcumin gel and honey on diabetic foot ulcer healing at Bilqis Clinic Bekasi. Design and Methods: A one-group pre-post experimental design was employed in the study. All 78 participants were selected using a complete sample procedure; the study population consisted of people with diabetic foot ulcers. Results: The age distribution of ozone group participants was 47.13 with a 23.14 standard deviation. The rising BMI averaged 26.17 (7.31). Many participants, 38 (55.1%), attended high school of the 48 people (77.4%), most had diabetes for less than three years. Patient glucose control was stable, averaging 121 (60.11) during the assessment. HbA1c was 10.29 (2.23), and basal wound size was 43.91 (21.45). The Wilcoxon test showed a significant difference (p=0.027 <0.05) between data gathered before and after using curcumin gel and honey. Conclusion: Curcumin and honey, when used as a wound treatment, has a notable impact on the healing process of diabetic foot ulcers. When treating chronic wounds, a mixture of curcumin and honey is suggested